PENGARUH MEDIA KOMIK TERHADAP PENGETAHUAN DAN SIKAP TENTANG SAYUR DAN BUAH DI SD AISYIYAH DAN SDN KALICILIK 2 DEMAK - Anjas Kusumarani; Astidio Noviardhi; Kun Aristiati Susiloretni (JURNAL RISET GIZI, 2018)
Background : Nutritional problems of lack of vegetables and fruits are common in primary school-aged children and have not been well socialized.Comics became one of the media that is very popular by children who have now been widely used as a medium of learning as well as entertainment. Provision of nutrition education through comic media is expected to increase knowledge and attitude about vegetables and fruits especially for elementary school children.  Objective  : To know the effect of nutrition education through comic media to knowledge and attitude about vegetables and fruit.  Method : This research usedquasy experimental design method with pre test post test group control design.The sample consisted of 32 treatment groups and 32 control groups. The collected data are psychosocial factor data (knowledge, attitude). The data were collected by using questionnaires filled in by respondents.The result of bivariate analysis using Man-Whitney test.  Results : There was a difference in knowledge increase in the treatment group and the control group before and after nutrition education through comic media (p 0,005) but there was no difference in attitude increase between the two groups (p 0,005).  Conclusion : Comic media on fruits and vegetables enhances knowledge and attitude in both groups. There is a difference in the improvement of the fraud between the treatment group and the control group. There was no difference in attitude improvement between the treatment group and the control group.